A preparation method of NFT@Fe / / NFT@MnFe flexible asymmetric plane interdigital supercapacitor

CN117912861BActive Publication Date: 2026-10-27NORTHEAST FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410203348.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-23
Publication Date
2026-10-27
Estimated Expiration
2044-02-23

AI Technical Summary

Technical Problem

但使用3D打印及丝网印刷等打印技术制备非对称型器件,需分步打印正负两极,该过程需对第二指状电极进行精确定位避免正负电极接触,这不可避免地增加了制造难度及成本

Benefits of technology

[0035]1、本发明将过渡金属氧化物纳米颗粒锚定在多壁碳纳米管表面,制备出具有优异电化学性能的活性材料MWCNT@Fe3O4与MWCNT@MnFe2O4,利用MWCNT的双电层电容、以及在Li2SO4电解质中Fe3O4、MnFe2O4表面发生的快速氧化还原反应,实现对电荷的高效储存与释放。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117912861B_ABST
    Figure CN117912861B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of an NFT@Fe / / NFT@MnFe flexible asymmetric plane interdigital supercapacitor, and relates to a preparation method of a supercapacitor. The purpose is to develop a novel flexible asymmetric plane interdigital supercapacitor, improve the area specific capacity and energy density of the supercapacitor, and lay an engineering foundation for the development of renewable, biocompatible and economically efficient flexible supercapacitors. In the application, transition metal oxide nanoparticles are anchored on the surface of multi-walled carbon nanotubes to prepare active materials MWCNT@Fe3O4 and MWCNT@MnFe2O4 with excellent electrochemical performance. The double-layer capacitance of MWCNT and the rapid oxidation-reduction reaction of Fe3O4 and MnFe2O4 on the surface in Li2SO4 electrolyte are utilized to realize efficient storage and release of electric charges.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a supercapacitor. Background Technology

[0002] Against the backdrop of a "dual carbon" environment, electricity has become a major development trend. The reversible storage and release of electrical energy is a key technology driving the continuous development of portable consumer electronics. Among various energy storage devices, supercapacitors have attracted widespread attention due to their advantages such as fast charging and discharging speeds, high power density, long cycle life, and wide operating temperature range, thus possessing potential application value in power transmission and high-power energy storage.

[0003] In recent years, the growing demand for wearable devices has driven the development of supercapacitors towards compactness, flexibility, and portability. Among these advancements, planar interdigitated devices have made significant contributions to the flexibility and miniaturization of supercapacitors. Compared to traditional sandwich-type device structures, planar interdigitated devices feature an interlaced electromechanical structure, which optimizes the electrode-electrolyte interface and reduces electrolyte ion transport resistance. Furthermore, the planar structure prevents displacement of different layers during bending, thereby improving the device's mechanical flexibility. Currently, various printing technologies are commonly used to construct interdigitated electrodes, including 3D printing, inkjet printing, roll-to-roll printing, screen printing, and stencil coating. Although significant progress has been made in the development of planar interdigitated supercapacitors based on electronic technology, developing devices that are renewable, environmentally friendly, cost-effective, and possess high specific capacitance and high energy density still presents challenges.

[0004] Currently, the development of planar finger-type supercapacitors using various printing technologies mainly revolves around constructing symmetrical devices. These supercapacitors are primarily double-layer capacitors, which, while possessing high power density, cannot achieve a large operating voltage window in aqueous electrolytes, thus limiting their energy density. Constructing asymmetric devices can effectively expand the operating voltage window and achieve the goal of increasing energy density. However, fabricating asymmetric devices using printing technologies such as 3D printing and screen printing requires printing the positive and negative electrodes step-by-step. This process necessitates precise positioning of the second finger electrode to avoid contact between the positive and negative electrodes, inevitably increasing manufacturing difficulty and cost. Furthermore, traditional printing inks require organic dispersants and binders, resulting in high costs and failing to meet the requirements for green and environmentally friendly devices. Summary of the Invention

[0005] The purpose of this invention is to develop a novel flexible asymmetric planar interdigitated supercapacitor, which improves the areal capacitance and energy density of supercapacitors, laying an engineering foundation for the development of renewable, bio-friendly, and cost-effective flexible supercapacitors.

[0006] The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor of the present invention is carried out according to the following steps:

[0007] I. Preparation of NFT@Fe Ink

[0008] ①, C 15 H 21 FeO6, multi-walled carbon nanotubes (MWCNTs) and triethylene glycol were placed in a three-necked flask and ultrasonically dispersed to obtain a uniformly dispersed suspension.

[0009] The C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is (0.38–0.42) g: (0.08–0.12) g: 30 mL;

[0010] ② Under nitrogen protection and stirring, the suspension is heated to 170-190℃ and kept at that temperature for 9-11 minutes to obtain a uniform black suspension.

[0011] ③ Heat the black suspension to the reflux temperature and reflux for 38–42 minutes;

[0012] The reflux temperature is 275–285°C;

[0013] The heating rate of the black suspension to reflux temperature is 8–12 °C / min;

[0014] ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@Fe3O4 nanocomposite material.

[0015] The grinding process is carried out to a particle size of 200μm to 250μm.

[0016] ⑤ Mix MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers (CNF) and deionized water, and disperse them by ultrasonication in an ultrasonic cell disruptor to obtain a uniform CNF / MWCNT / MWCNT@Fe3O4 ink;

[0017] The ratio of the MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is: (75-79) mg: (9-13) mg: (20-24) mg: 10 mL;

[0018] II. Preparation of NFT@MnFe Ink

[0019] ①, Mix Mn(CH2COOH)2 and C 15 H 21 FeO6, multi-walled carbon nanotubes and triethylene glycol were ultrasonically dispersed to obtain a suspension.

[0020] The Mn(CH2COOH)2, C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is (0.12–0.16) g: (0.38–0.42) g: (0.08–0.12) g: 30 mL;

[0021] ② Under nitrogen protection and stirring, the suspension is heated to 170-190℃ and kept at that temperature for 9-11 minutes to obtain a uniform black suspension.

[0022] ③ Heat the black suspension to the reflux temperature and reflux for 38–42 minutes;

[0023] The reflux temperature is 275–285°C;

[0024] The heating rate of the black suspension to reflux temperature is 8–12 °C / min;

[0025] ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@MnFe2O4 nanocomposite material.

[0026] The grinding process is carried out to a particle size of 200μm to 250μm.

[0027] ⑤ Mix MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water, and disperse them by ultrasonication in an ultrasonic cell disruptor to obtain uniform CNF / MWCNT / MWCNT@MnFe2O4 ink;

[0028] The ratio of the MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is: (54-58) mg: (6-10) mg: (14-18) mg: 10 mL;

[0029] III. Assembly of Supercapacitors

[0030] ① A layer of mixed cellulose filter membrane is laid in a sand core funnel. Then, a metal mask plate with interdigitated electrode pattern is laid on the mixed cellulose filter membrane. CNF / MWCNT / MWCNT@MnFe2O4 ink is coated on the positive electrode part of the interdigitated electrode pattern, and CNF / MWCNT / MWCNT@Fe3O4 ink is coated on the negative electrode part of the interdigitated electrode pattern. Then, vacuum filtration is performed. After completion, it is dried at room temperature to form an asymmetric interdigitated electrode on the mixed cellulose filter membrane.

[0031] The coating amount of CNF / MWCNT / MWCNT@Fe3O4 ink and CNF / MWCNT / MWCNT@MnFe2O4 ink is the same, ranging from 50 μL to 250 μL;

[0032] ② Transfer the asymmetric interdigitated electrode to the adhesive layer of PET tape (the interdigitated electrode is adhered to the adhesive layer of PET tape), connect the positive and negative electrodes of the asymmetric interdigitated electrode to the tabs respectively, and finally cover it with carboxymethyl cellulose / Li2SO4 (CMC / Li2SO4) gel electrolyte to obtain an asymmetric interdigitated electrode with gel electrolyte.

[0033] ③ By encapsulating asymmetric interdigitated fingers with gel electrolyte using PET tape, a single-layer asymmetric planar interdigitated asymmetric supercapacitor can be obtained; or by attaching one side of the carboxymethyl cellulose / Li2SO4 gel electrolyte of two asymmetric interdigitated fingers together, connecting the positive electrodes of the two interdigitated fingers together, and connecting the negative electrodes of the two interdigitated fingers together, a double-layer asymmetric planar interdigitated asymmetric supercapacitor can be formed.

[0034] The principle and beneficial effects of this invention are as follows:

[0035] 1. This invention anchors transition metal oxide nanoparticles onto the surface of multi-walled carbon nanotubes to prepare active materials MWCNT@Fe3O4 and MWCNT@MnFe2O4 with excellent electrochemical performance. By utilizing the double-layer capacitance of MWCNTs and the rapid redox reaction that occurs on the surfaces of Fe3O4 and MnFe2O4 in Li2SO4 electrolyte, efficient storage and release of charge can be achieved.

[0036] 2. This invention uses cellulose nanofibers to replace traditional dispersants and binders. Cellulose nanofibers are natural polymers that are green, environmentally friendly, and biodegradable, avoiding the use of non-environmentally friendly organic solvents. Therefore, they have the advantages of being green, environmentally friendly, biodegradable, and recyclable, laying an engineering foundation for the development of renewable, bio-friendly, and cost-effective flexible supercapacitors.

[0037] 3. This invention achieves the preparation of uniform and stable electrode ink and successfully establishes a 3D conductive network between CNF and MWCNT@Fe, and between CNF and MWCNT@MnFe. This conductive network can improve the electrode-electrolyte interface on the one hand, and provide a pathway for charge transport and electrolyte ion migration on the other hand, thereby preparing a high-performance flexible electrode and developing a high-performance flexible supercapacitor based on it.

[0038] 4. Compared with printing technologies such as 3D printing and inkjet printing, the metal mask plate combined with vacuum filtration process used in this invention is simple, convenient, low-cost, requires low ink viscosity, and has a fast preparation speed. It can prepare asymmetric interdigitated electrodes in one step without the need to position the second electrode and effectively reduce production costs.

[0039] 5. Compared to existing planar interdigitated supercapacitors, the asymmetric flexible device prepared in this invention exhibits higher areal capacitance and energy density. Furthermore, the specific capacitance and energy density of the device can be controlled by altering the amount of ink used to change the loading of active material per unit area.

[0040] 6. Traditional asymmetric devices are rigid devices that require current collectors such as carbon cloth and nickel foam. This invention develops a novel flexible asymmetric supercapacitor. The electrodes in this device are self-supporting electrodes, eliminating the need for additional current collectors and reducing the device's "dead" mass and manufacturing cost.

[0041] 7. This invention has strong scalability and integrability, and can realize the series and parallel connection of multiple devices. It can also realize the construction of customized patterned planar electrodes by changing the mask template. Attached Figure Description

[0042] Figure 1 This is a schematic diagram of the asymmetric interdigitated electrode obtained in step three ① of Example 1;

[0043] Figure 2 This is a schematic diagram of the asymmetric interdigitated structure with gel electrolyte obtained in step 3 ② of Example 1;

[0044] Figure 3 This is a schematic diagram of the single-layer asymmetric planar interdigitated asymmetric supercapacitor structure obtained in step 3③ of Example 1;

[0045] Figure 4 This is a schematic diagram of the double-layer asymmetric planar interdigitated asymmetric supercapacitor structure obtained in step 3③ of Example 1;

[0046] Figure 5 The image shows the physical diagram of the asymmetric interdigitated electrode obtained in step 3① of Example 1.

[0047] Figure 6Cyclic voltammetry curves (5 mV / s) of the supercapacitor prepared in Example 1 at different ink volumes. -1 );

[0048] Figure 7 Cyclic voltammetry curves of a supercapacitor (NFT@Fe / / NFT@MnFe-250) with an ink volume of 250 μL prepared in Example 1 at different scan rates;

[0049] Figure 8 The NFT@Fe / / NFT@MnFe-250 and NFT@Fe / / NFT@MnFe-250D prepared in Example 1 were subjected to 5 mV / s -1 Cyclic voltammetry curve at scan rate. Detailed Implementation

[0050] The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any reasonable combination of the specific embodiments.

[0051] Specific Implementation Method 1: The fabrication method of the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor in this implementation method is carried out according to the following steps:

[0052] I. Preparation of NFT@Fe Ink

[0053] ①, C 15 H 21 FeO6, multi-walled carbon nanotubes (MWCNTs) and triethylene glycol were placed in a three-necked flask and ultrasonically dispersed to obtain a uniformly dispersed suspension.

[0054] The C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is (0.38–0.42) g: (0.08–0.12) g: 30 mL;

[0055] ② Under nitrogen protection and stirring, the suspension is heated to 170-190℃ and kept at that temperature for 9-11 minutes to obtain a uniform black suspension.

[0056] ③ Heat the black suspension to the reflux temperature and reflux for 38–42 minutes;

[0057] The reflux temperature is 275–285°C;

[0058] The heating rate of the black suspension to reflux temperature is 8–12 °C / min;

[0059] ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@Fe3O4 nanocomposite material.

[0060] The grinding process is carried out to a particle size of 200μm to 250μm.

[0061] ⑤ Mix MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers (CNF) and deionized water, and disperse them by ultrasonication in an ultrasonic cell disruptor to obtain a uniform CNF / MWCNT / MWCNT@Fe3O4 ink;

[0062] The ratio of the MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is: (75-79) mg: (9-13) mg: (20-24) mg: 10 mL;

[0063] II. Preparation of NFT@MnFe Ink

[0064] ①, Mix Mn(CH2COOH)2 and C 15 H 21 FeO6, multi-walled carbon nanotubes and triethylene glycol were ultrasonically dispersed to obtain a suspension.

[0065] The Mn(CH2COOH)2, C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is (0.12–0.16) g: (0.38–0.42) g: (0.08–0.12) g: 30 mL;

[0066] ② Under nitrogen protection and stirring, the suspension is heated to 170-190℃ and kept at that temperature for 9-11 minutes to obtain a uniform black suspension.

[0067] ③ Heat the black suspension to the reflux temperature and reflux for 38–42 minutes;

[0068] The reflux temperature is 275–285°C;

[0069] The heating rate of the black suspension to reflux temperature is 8–12 °C / min;

[0070] ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@MnFe2O4 nanocomposite material.

[0071] The grinding process is carried out to 200μm~250μm;

[0072] ⑤ Mix MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water, and disperse them by ultrasonication in an ultrasonic cell disruptor to obtain uniform CNF / MWCNT / MWCNT@MnFe2O4 ink;

[0073] The ratio of the MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is: (54-58) mg: (6-10) mg: (14-18) mg: 10 mL;

[0074] III. Assembly of Supercapacitors

[0075] ① A layer of mixed cellulose filter membrane is laid in a sand core funnel. Then, a metal mask plate with interdigitated electrode pattern is laid on the mixed cellulose filter membrane. CNF / MWCNT / MWCNT@MnFe2O4 ink is coated on the positive electrode part of the interdigitated electrode pattern, and CNF / MWCNT / MWCNT@Fe3O4 ink is coated on the negative electrode part of the interdigitated electrode pattern. Then, vacuum filtration is performed. After completion, it is dried at room temperature to form an asymmetric interdigitated electrode on the mixed cellulose filter membrane.

[0076] The coating amount of CNF / MWCNT / MWCNT@Fe3O4 ink and CNF / MWCNT / MWCNT@MnFe2O4 ink is the same, ranging from 50 μL to 250 μL;

[0077] ② Transfer the asymmetric interdigitated electrode to the adhesive layer of PET tape (the interdigitated electrode is adhered to the adhesive layer of PET tape), connect the positive and negative electrodes of the asymmetric interdigitated electrode to the tabs respectively, and finally cover it with carboxymethyl cellulose / Li2SO4 (CMC / Li2SO4) gel electrolyte to obtain an asymmetric interdigitated electrode with gel electrolyte.

[0078] ③ By encapsulating asymmetric interdigitated fingers with gel electrolyte using PET tape, a single-layer asymmetric planar interdigitated asymmetric supercapacitor can be obtained; or by attaching one side of the carboxymethyl cellulose / Li2SO4 gel electrolyte of two asymmetric interdigitated fingers together, connecting the positive electrodes of the two interdigitated fingers together, and connecting the negative electrodes of the two interdigitated fingers together, a double-layer asymmetric planar interdigitated asymmetric supercapacitor can be formed.

[0079] This embodiment has the following beneficial effects:

[0080] 1. In this embodiment, transition metal oxide nanoparticles are anchored on the surface of multi-walled carbon nanotubes to prepare active materials MWCNT@Fe3O4 and MWCNT@MnFe2O4 with excellent electrochemical performance. By utilizing the double-layer capacitance of MWCNT and the rapid redox reaction that occurs on the surface of Fe3O4 and MnFe2O4 in Li2SO4 electrolyte, efficient storage and release of charge can be achieved.

[0081] 2. This embodiment uses cellulose nanofibers to replace traditional dispersants and binders. Cellulose nanofibers are natural polymers that are green, environmentally friendly, and biodegradable, avoiding the use of non-environmentally friendly organic solvents. Therefore, they have the advantages of being green, environmentally friendly, biodegradable, and recyclable, laying an engineering foundation for the development of renewable, bio-friendly, and cost-effective flexible supercapacitors.

[0082] 3. This embodiment achieves the preparation of uniform and stable electrode ink and successfully establishes a 3D conductive network between CNF and MWCNT@Fe, and between CNF and MWCNT@MnFe. This conductive network can improve the electrode-electrolyte interface on the one hand, and provide a pathway for charge transport and electrolyte ion migration on the other hand, thereby preparing a high-performance flexible electrode and developing a high-performance flexible supercapacitor based on it.

[0083] 4. Compared with printing technologies such as 3D printing and inkjet printing, the metal mask plate combined with vacuum filtration process used in this embodiment is simple, convenient, low-cost, requires low ink viscosity, and has a fast preparation speed. It can prepare asymmetric interdigitated electrodes in one step without the need to position the second electrode and effectively reduce production costs.

[0084] 5. Compared to existing planar interdigitated supercapacitors, the asymmetric flexible device prepared in this embodiment has higher areal capacitance and energy density. Furthermore, the specific capacitance and energy density of the device can be controlled by varying the amount of ink used to change the loading of active material per unit area.

[0085] 6. Traditional asymmetric devices are rigid devices that require current collectors such as carbon cloth and nickel foam. This embodiment develops a novel flexible asymmetric supercapacitor. The electrodes in this device are self-supporting electrodes, eliminating the need for additional current collectors and reducing the device's "dead" mass and manufacturing cost.

[0086] 7. This implementation method has strong scalability and integrability, and can realize the series and parallel connection of multiple devices. It can also realize the construction of customized patterned planar electrodes by changing the mask template.

[0087] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that: the ultrasonic dispersion process in step one ① is: ultrasonic dispersion for 38-42 minutes at a power of 300W.

[0088] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 1 or 2 in that the heating rate during step 1 ② is 1-3℃ / min.

[0089] Specific Implementation Method Four: This implementation method differs from one of the specific implementation methods one to three in that the drying process described in step one ④ is: drying at 50°C for 4 hours.

[0090] Specific Implementation Method 5: This implementation method differs from one of the specific implementation methods 1 to 4 in that the ultrasonic dispersion process described in step 1 (⑤) is as follows: ultrasonic dispersion for 10 minutes at a power of 300W.

[0091] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the ultrasonic dispersion process in step two① is as follows: ultrasonic dispersion for 38 to 42 minutes at a power of 300W.

[0092] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the heating rate during step 2② is 1 to 3 °C / min.

[0093] Specific Implementation Method Eight: This implementation method differs from one of the specific implementation methods one to seven in that the drying process described in step two ④ is: drying at 50°C for 4 hours.

[0094] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the ultrasonic dispersion process described in step two (⑤) is as follows: ultrasonic dispersion for 10 minutes at a power of 300W.

[0095] Specific Implementation Method 10: This implementation method differs from Specific Implementation Methods 1 to 9 in that the mass ratio of carboxymethyl cellulose, Li2SO4 and deionized water in the carboxymethyl cellulose / Li2SO4 gel electrolyte in step 3② is 0.3g:1.92g:15g.

[0096] Example 1:

[0097] The fabrication method of the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor in this embodiment is carried out according to the following steps:

[0098] I. Preparation of NFT@Fe Ink

[0099] ①, C 15 H 21FeO6, multi-walled carbon nanotubes (MWCNTs) and triethylene glycol were placed in a three-necked flask and ultrasonically dispersed to obtain a uniformly dispersed suspension.

[0100] The C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is 0.40 g: 0.10 g: 30 mL;

[0101] The ultrasonic dispersion process is as follows: ultrasonic dispersion for 40 minutes at a power of 300W.

[0102] ② Under nitrogen protection and stirring, the suspension was heated to 180°C and kept at that temperature for 10 minutes to obtain a uniform black suspension.

[0103] The heating rate at which the temperature is raised is 2°C / min;

[0104] ③ Heat the black suspension to the reflux temperature and reflux for 40 minutes;

[0105] The reflux temperature is 280°C;

[0106] The heating rate of the black suspension to reflux temperature is 10℃ / min;

[0107] ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@Fe3O4 nanocomposite material.

[0108] The drying process is as follows: drying at 50℃ for 4 hours;

[0109] The grinding process is carried out to a particle size of 200 μm;

[0110] ⑤ Mix MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers (CNF) and deionized water, and disperse them by ultrasonication in an ultrasonic cell disruptor to obtain a uniform CNF / MWCNT / MWCNT@Fe3O4 ink;

[0111] The ratio of the MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is 77mg:11mg:22mg:10mL;

[0112] The ultrasonic dispersion process is as follows: ultrasonic dispersion for 10 minutes at a power of 300W;

[0113] II. Preparation of NFT@MnFe Ink

[0114] ①, Mix Mn(CH2COOH)2 and C 15 H 21 FeO6, multi-walled carbon nanotubes and triethylene glycol were ultrasonically dispersed to obtain a suspension.

[0115] The Mn(CH2COOH)2, C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is 0.14g:0.40g:0.1g:30mL;

[0116] The ultrasonic dispersion process is as follows: ultrasonic dispersion for 40 minutes at a power of 300W.

[0117] ② Under nitrogen protection and stirring, the suspension was heated to 180°C and kept at that temperature for 10 minutes to obtain a uniform black suspension.

[0118] The heating rate at which the temperature is raised is 2°C / min;

[0119] ③ Heat the black suspension to the reflux temperature and reflux for 40 minutes;

[0120] The reflux temperature is 280°C;

[0121] The heating rate of the black suspension to reflux temperature is 10℃ / min;

[0122] ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@MnFe2O4 nanocomposite material.

[0123] The drying process is as follows: drying at 50℃ for 4 hours;

[0124] The material is ground to 200μm;

[0125] ⑤ Mix MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water, and disperse them by ultrasonication in an ultrasonic cell disruptor to obtain uniform CNF / MWCNT / MWCNT@MnFe2O4 ink;

[0126] The ratio of the MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is 56mg:8mg:16mg:10mL;

[0127] The ultrasonic dispersion process is as follows: ultrasonic dispersion for 10 minutes at a power of 300W;

[0128] III. Assembly of Supercapacitors

[0129] ① A layer of mixed cellulose filter membrane is laid in a sand core funnel. Then, a metal mask plate with interdigitated electrode pattern is laid on the mixed cellulose filter membrane. CNF / MWCNT / MWCNT@MnFe2O4 ink is coated on the positive electrode part of the interdigitated electrode pattern, and CNF / MWCNT / MWCNT@Fe3O4 ink is coated on the negative electrode part of the interdigitated electrode pattern. Then, vacuum filtration is performed. After completion, it is dried at room temperature to form an asymmetric interdigitated electrode on the mixed cellulose filter membrane.

[0130] The coating amounts of the CNF / MWCNT / MWCNT@Fe3O4 ink and the CNF / MWCNT / MWCNT@MnFe2O4 ink are 50 μL, 100 μL, 150 μL, 200 μL, and 250 μL, respectively.

[0131] ② Transfer the asymmetric interdigitated electrode to the adhesive layer of PET tape (the interdigitated electrode is adhered to the adhesive layer of PET tape), connect the positive and negative electrodes of the asymmetric interdigitated electrode to the tabs respectively, and finally cover it with carboxymethyl cellulose / Li2SO4 (CMC / Li2SO4) gel electrolyte to obtain an asymmetric interdigitated electrode with gel electrolyte.

[0132] The mass ratio of carboxymethyl cellulose, Li2SO4, and deionized water in the carboxymethyl cellulose / Li2SO4 gel electrolyte is 0.3g:1.92g:15g.

[0133] ③ By encapsulating asymmetric interdigitated fingers with gel electrolyte using PET tape, a single-layer asymmetric planar interdigitated asymmetric supercapacitor is obtained; the ink coating amounts are 50μL, 100μL, 150μL, 200μL, and 250μL, respectively, corresponding to the single-layer asymmetric planar interdigitated asymmetric supercapacitors NFT@Fe / / NFT@MnFe-50, NFT@Fe / / NFT@MnFe-100, NFT@Fe / / NFT@MnFe-150, NFT@Fe / / NFT@MnFe-200, and NFT@Fe / / NFT@MnFe-250;

[0134] Two asymmetric interdigitated carboxymethyl cellulose / Li2SO4 gel electrolytes are bonded together on one side, and the positive electrodes of the two interdigitated electrodes are connected together, and the negative electrodes of the two interdigitated electrodes are connected together to form a double-layer asymmetric planar interdigitated asymmetric supercapacitor (NFT@Fe / / NFT@MnFe-250D).

[0135] Figure 1 This is a schematic diagram of the asymmetric interdigitated electrode obtained in step three ① of Example 1; Figure 2This is a schematic diagram of the asymmetric interdigitated structure with gel electrolyte obtained in step 3 ② of Example 1; Figure 3 This is a schematic diagram of the single-layer asymmetric planar interdigitated asymmetric supercapacitor structure obtained in step 3③ of Example 1; Figure 4 This is a schematic diagram of the double-layer asymmetric planar interdigitated asymmetric supercapacitor structure obtained in step 3③ of Example 1; Figure 5 The image shows the physical diagram of the asymmetric interdigitated electrode obtained in step 3① of Example 1. Figure 6 Cyclic voltammetry curves (5 mV / s) of the supercapacitor prepared in Example 1 at different ink volumes. -1 ); Figure 6 It can be seen that at 5mVs -1 At the specified scan rate, the areal specific capacities of NFT@Fe / / NFT@MnFe-250, NFT@Fe / / NFT@MnFe-200, NFT@Fe / / NFT@MnFe-150, NFT@Fe / / NFT@MnFe-100, and NFT@Fe / / NFT@MnFe-50 were 392.0 mF / cm². -2 ;294.8mFcm -2 232.3mFcm -2 186.5mFcm -2 and 122.4mFcm -2 . Figure 7 Cyclic voltammetry curves of a 250 μL supercapacitor (NFT@Fe / / NFT@MnFe-250) prepared in Example 1 at different scan rates; according to Figure 7 Test results, at 50mVs -1 The shape of the cyclic voltammetry curve of the device did not change significantly within the scan rate of 50 mVs. -1 It still has a scan rate of 140.3 mFcm. -2 The area is greater than the capacity. Figure 8 The NFT@Fe / / NFT@MnFe-250 and NFT@Fe / / NFT@MnFe-250D prepared in Example 1 were subjected to 5 mV / s -1 Cyclic voltammetry curve at scan rate; Figure 8 It can be seen that NFT@Fe / / NFT@MnFe-250D has a larger isometric capacity, at 991.8 mF / cm². -2 .

Claims

1. A method for fabricating a flexible asymmetric planar interdigitated supercapacitor using NFT@Fe / / NFT@MnFe, characterized in that: The fabrication method of NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor is carried out according to the following steps: I. Preparation of NFT@Fe Ink ①, C 15 H 21 FeO6, multi-walled carbon nanotubes (MWCNTs) and triethylene glycol were placed in a three-necked flask and ultrasonically dispersed to obtain a uniformly dispersed suspension. The C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is (0.38~0.42)g:(0.08~0.12)g:30mL; ② Under nitrogen protection and stirring, the suspension is heated to 170~190℃ and kept at that temperature for 9~11 minutes to obtain a uniform black suspension; ③ Heat the black suspension to the reflux temperature and reflux for 38-42 minutes; The reflux temperature is 275~285℃; The heating rate of the black suspension to reflux temperature is 8~12℃ / min; ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@Fe3O4 nanocomposite material. The grinding process is carried out to a particle size of 200μm~250μm; ⑤ Mix MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers (CNF) and deionized water, and disperse them ultrasonically using an ultrasonic cell disruptor to obtain a uniform CNF / MWCNT / MWCNT@Fe3O4 ink; The ratio of the MWCNT@Fe3O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is (75~79)mg:(9~13)mg:(20~24)mg:10mL; II. Preparation of NFT@MnFe Ink ①, Mix Mn(CH2COOH)2 and C 15 H 21 FeO6, multi-walled carbon nanotubes and triethylene glycol were ultrasonically dispersed to obtain a suspension. The Mn(CH2COOH)2, C 15 H 21 The ratio of FeO6, multi-walled carbon nanotubes, and triethylene glycol is (0.12~0.16)g:(0.38~0.42)g:(0.08~0.12)g:30mL; ② Under nitrogen protection and stirring, the suspension is heated to 170~190℃ and kept at that temperature for 9~11 minutes to obtain a uniform black suspension; ③ Heat the black suspension to the reflux temperature and reflux for 38-42 minutes; The reflux temperature is 275~285℃; The heating rate of the black suspension to reflux temperature is 8~12℃ / min; ④ The solution obtained by reflux was naturally cooled to room temperature to separate the black solid. Then the black solid was washed with anhydrous ethanol and magnetic separation was performed using a magnet to remove unreacted multi-walled carbon nanotubes and reaction byproducts. Finally, the black solid product was dried and ground to obtain MWCNT@MnFe2O4 nanocomposite material. The grinding process is carried out to a particle size of 200μm~250μm; ⑤ Mix MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water, and disperse them ultrasonically using an ultrasonic cell disruptor to obtain uniform CNF / MWCNT / MWCNT@MnFe2O4 ink; The ratio of the MWCNT@MnFe2O4 nanocomposite material, multi-walled carbon nanotubes, cellulose nanofibers and deionized water is: (54~58)mg:(6~10)mg:(14~18)mg:10mL; III. Assembly of Supercapacitors ① A layer of mixed cellulose filter membrane is laid in a sand core funnel. Then, a metal mask plate with interdigitated electrode pattern is laid on the mixed cellulose filter membrane. CNF / MWCNT / MWCNT@MnFe2O4 ink is coated on the positive electrode part of the interdigitated electrode pattern, and CNF / MWCNT / MWCNT@Fe3O4 ink is coated on the negative electrode part of the interdigitated electrode pattern. Then, vacuum filtration is performed. After completion, it is dried at room temperature to form an asymmetric interdigitated electrode on the mixed cellulose filter membrane. The coating amount of CNF / MWCNT / MWCNT@Fe3O4 ink and CNF / MWCNT / MWCNT@MnFe2O4 ink is the same, ranging from 50 μL to 250 μL; ② Transfer the asymmetric interdigitated electrode to the adhesive layer of PET tape. The interdigitated electrode is adhered to the adhesive layer of PET tape. The positive and negative electrodes of the asymmetric interdigitated electrode are connected to the tabs respectively. Finally, cover with carboxymethyl cellulose / Li2SO4 (CMC / Li2SO4) gel electrolyte to obtain an asymmetric interdigitated electrode with gel electrolyte. ③ By encapsulating asymmetric interdigitated fingers with gel electrolyte using PET tape, a single-layer asymmetric planar interdigitated asymmetric supercapacitor can be obtained; or by attaching one side of the carboxymethyl cellulose / Li2SO4 gel electrolyte of two asymmetric interdigitated fingers together, connecting the positive electrodes of the two interdigitated fingers together, and connecting the negative electrodes of the two interdigitated fingers together, a double-layer asymmetric planar interdigitated asymmetric supercapacitor can be formed.

2. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: Step 1① The ultrasonic dispersion process is as follows: ultrasonic dispersion for 38~42 minutes at a power of 300W.

3. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: The heating rate in step 1② is 1~3℃ / min.

4. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: The drying process described in step 1, ④, involves drying at 50°C for 4 hours.

5. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: The ultrasonic dispersion process described in step 1, step 5, is as follows: ultrasonic dispersion for 10 minutes at a power of 300W.

6. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: Step 2① The ultrasonic dispersion process is as follows: ultrasonic dispersion for 38~42 minutes at a power of 300W.

7. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: The heating rate in step 2② is 1~3℃ / min.

8. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: Step 2, ④, involves drying at 50°C for 4 hours.

9. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: The ultrasonic dispersion process described in step 2.5 is as follows: ultrasonic dispersion for 10 minutes at a power of 300W.

10. The method for fabricating the NFT@Fe / / NFT@MnFe flexible asymmetric planar interdigitated supercapacitor according to claim 1, characterized in that: In step 3②, the mass ratio of carboxymethyl cellulose, Li2SO4, and deionized water in the carboxymethyl cellulose / Li2SO4 gel electrolyte is 0.3g:1.92g:15g.

Citation Information

Patent Citations

  • MnO2 and Fe2O3 nanostructure-based flexible asymmetric super-capacitor and preparation method as well as application thereof

    CN103366970A

  • Capacitor electrode foil and capacitor

    CN110770862A